2019
DOI: 10.1002/pssr.201900135
|View full text |Cite
|
Sign up to set email alerts
|

Spin Reversal Mechanism of a Perpendicular Exchange Bias System with an Antiferromagnet Incorporating a Parasitic Ferromagnetism

Abstract: Aluminum doping produced the parasitic magnetization (M para ) with high coercivity in 20 nm thin antiferromagnetic Cr 2 O 3 films. By using the large coercive force of M para , whose direction is the same as the antiferromagnetic Cr 2 O 3 surface spin, antiferromagnetic spin reversal can be detected through the vertical shift of the hysteresis loop of an antiferromagnetic-Cr 2 O 3 / ferromagnet perpendicular exchange bias (PEB) coupling system. By analyzing both antiferromagnetic and ferromagnetic spin revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(28 citation statements)
references
References 37 publications
(48 reference statements)
6
22
0
Order By: Relevance
“…Although Cr 2 O 3 is an antiferromagnet, it has a net boundary magnetism in its surface that is independent of surface morphology and contributes significantly to its ME effect. [43][44][45][46][47][48][49] Al doping induces a high-coercivity parasitic magnetism (intrinsically, it is a volume-dependent net boundary magnetism) along the same direction to the top-surface AFM spin of Cr 2 O 3 ; [50,51] this phenomenon has been used to track AFM spin reversal during the perpendicular exchange bias process. Based on this method, [50,51] it was found that the spin direction of Cr 2 O 3 in a Cr 2 O 3 /ferromagnet exchange-coupling system is determined by the competition between the Zeeman energy of net boundary magnetism of Cr 2 O 3 and exchange-coupling energy.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although Cr 2 O 3 is an antiferromagnet, it has a net boundary magnetism in its surface that is independent of surface morphology and contributes significantly to its ME effect. [43][44][45][46][47][48][49] Al doping induces a high-coercivity parasitic magnetism (intrinsically, it is a volume-dependent net boundary magnetism) along the same direction to the top-surface AFM spin of Cr 2 O 3 ; [50,51] this phenomenon has been used to track AFM spin reversal during the perpendicular exchange bias process. Based on this method, [50,51] it was found that the spin direction of Cr 2 O 3 in a Cr 2 O 3 /ferromagnet exchange-coupling system is determined by the competition between the Zeeman energy of net boundary magnetism of Cr 2 O 3 and exchange-coupling energy.…”
Section: Resultsmentioning
confidence: 99%
“…[43][44][45][46][47][48][49] Al doping induces a high-coercivity parasitic magnetism (intrinsically, it is a volume-dependent net boundary magnetism) along the same direction to the top-surface AFM spin of Cr 2 O 3 ; [50,51] this phenomenon has been used to track AFM spin reversal during the perpendicular exchange bias process. Based on this method, [50,51] it was found that the spin direction of Cr 2 O 3 in a Cr 2 O 3 /ferromagnet exchange-coupling system is determined by the competition between the Zeeman energy of net boundary magnetism of Cr 2 O 3 and exchange-coupling energy. Therefore, assuming that sufficient external (magnetic or electric) fields are applied, and a single AFM domain is obtained, a downward topsurface spin of Cr 2 O 3 could result in a negative exchange bias for Cr 2 O 3 /ferromagnet exchange-coupling system (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations